Ontology Mapping using Fuzzy Decision Tree and Formal Concept Analysis (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
An ontology describes and defines the terms used to describe and represent an area of knowledge. Different people or organizations come up with their own ontology; having their own view of the domain. So, for systems to interoperate, it becomes necessary to map these heterogeneous ontologies.This paper discusses the state of the art methods and outlines a new approach with improved precision and recall. Also the system finds other than 1:1 relationships.